Kemampuan Komunikasi Matematis dalam Menyelesaikan Soal Cerita Ditinjau dari Tipe Kepribadian Extrovert dan Introvert - Izzati Hilmi, Nida; Turmuzi, Muhammad; Humaira Salsabila, Nilza (Pendidikan Matematika FKIP Universitas Mataram, 2025)
This study aims to describe students’ mathematical communication skills in the topic of two variable linear equation systems, viewed from the perspective of extrovert and introvert personality types among eighth-grade students at SMPN 1 Labupi. This type of research is qualitative with a descriptive method. The research instruments consisted of a questionnaire, a test, and interview guidelines. Of the 34 students who completed the personality type questionnaire, 14 were identified as extroverts and 20 as introverts. Subsequently, the students were given a mathematical communication skills test. Based on the results, four research subjects were selected, consisting of two extroverted students and two introverted students. The qualitative data analysis used in this study consists of three stages: data reduction, data presentation, and drawing conclusions. The results showed that both high and low level extrovert students demonstrated good mathematical communication skills, as they were able to meet the indicators of mathematical communication skills, namely writing, reading, and mathematical expression. Extroverted students were more proficient in explaining problem solutions compared to introverted students. High-level introverted students also showed good mathematical communication skills, fulfilling the aspects of writing, reading, and mathematical expression. Meanwhile, low-level introverted students were only able to fulfill the writing aspect and still experienced difficulties in meeting the reading and mathematical expression aspects.